Resilient health care. - Wears, Robert L.; Hollnagel, Erik, 1941-; Braithwaite, Jeffrey, 1954- (Ashgate studies in resilience engineering., 2015)
Health care is everywhere under tremendous pressure with regard to efficiency, safety, and economic viability - to say nothing of having to meet various political agendas - and has responded by eagerly adopting techniques that have been useful in other industries, such as quality management, lean production, and high reliability. This has on the whole been met with limited success because health care as a non-trivial and multifaceted system differs significantly from most traditional industries. In order to allow health care systems to perform as expected and required, it is necessary to have concepts and methods that are able to cope with this complexity. Resilience engineering provides that capacity because its focus is on a system's overall ability to sustain required operations under both expected and unexpected conditions rather than on individual features or qualities. Resilience engineering's unique approach emphasises the usefulness of performance variability, and that successes and failures have the same aetiology. This book contains contributions from acknowledged international experts in health care, organisational studies and patient safety, as well as resilience engineering. Whereas current safety approaches primarily aim to reduce or eliminate the number of things that go wrong, Resilient Health Care aims to increase and improve the number of things that go right. Just as the WHO argues that health is more than the absence of illness, so does Resilient Health Care argue that safety is more than the absence of risk and accidents. This can be achieved by making use of the concrete experiences of resilience engineering, both conceptually (ways of thinking) and practically (ways of acting).